2007
DOI: 10.1097/nen.0b013e31815c5efb
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Correlations in a Large Alzheimer Disease Center Autopsy Cohort

Abstract: There is uncertainty regarding the association of cognitive decline in Alzheimer disease (AD) with classic histopathologic features- neurofibrillary tangles (NFTs) and "neuritic" amyloid plaques (NPs). This uncertainty fuels doubts about the diagnostic importance of NFTs and NPs and leads to confusion regarding hypotheses of AD pathogenesis. Three hundred ninety subjects who underwent longitudinal premortem clinical workup and postmortem quantitative neuropathologic assessment served as the group to address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
163
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(183 citation statements)
references
References 83 publications
11
163
0
Order By: Relevance
“…Although cognitively normal elderly may show variable neocortical AD-related pathology, in general, the number of isocortical tangles correlates best with the severity of cognitive impairment (Nelson et al, 2007;Nelson et al, 2009;Markesbery, 2010;Nelson et al, 2012). The pattern of gray matter loss associated with tangle pathology is an appropriate in vivo surrogate indicator of AD pathology (Whitwell et al, 2008).…”
Section: Specific Problems In the Diagnosis Of Alzheimer Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Although cognitively normal elderly may show variable neocortical AD-related pathology, in general, the number of isocortical tangles correlates best with the severity of cognitive impairment (Nelson et al, 2007;Nelson et al, 2009;Markesbery, 2010;Nelson et al, 2012). The pattern of gray matter loss associated with tangle pathology is an appropriate in vivo surrogate indicator of AD pathology (Whitwell et al, 2008).…”
Section: Specific Problems In the Diagnosis Of Alzheimer Diseasementioning
confidence: 99%
“…The pattern of gray matter loss associated with tangle pathology is an appropriate in vivo surrogate indicator of AD pathology (Whitwell et al, 2008). The predictive value of widespread tau pathology (Braak stages V-VI) for dementia is high (Nelson et al, 2007;Nelson et al, 2012), while others found that both diffuse and neuritic plaques, rather than tangles in neocortical regions distinguish nondemented and AD subjects with high sensitivity and specificity (McKeel et al, 2004). A recent study found that the amyloid stage that has progressed to involve the striatum is highly predictive of dementia .…”
Section: Specific Problems In the Diagnosis Of Alzheimer Diseasementioning
confidence: 99%
“…Such DNA damage could potently lead to the loss of ribosomal DNA copies. Alzheimer's Disease Center cohort and were followed for at least 2 years before death [53]. The follow up included annual Minimental State Examination as well as neurological and physical examinations.…”
Section: Introductionmentioning
confidence: 99%
“…The Minimental State Examination score closest to death was used as an indicator of overall cognitive status. During autopsy (usually 5 or less hours after death), tissue samples including parietal cortex and cerebellum were processed for neuropathological evaluations or flash-frozen in liquid nitrogen and stored at -80°C, as described previously [53,54]. All included Dementia with Lewy Bodies subjects met the clinical and histopathological criteria for diagnosis of Dementia with Lewy Bodies [55].…”
Section: Introductionmentioning
confidence: 99%
“…According to Braak et al 9 , the presence of tau deposits is classified in six stages, from I to VI, beginning with the transentorhinal region (stage I) and progressing until stage VI with severe pathology of the isocortex. Late phases of the disease cause recognizable symptoms and have been correlated with the clinical manifestations of AD 6,10,11 . However, studies of these phases have been laden with difficulties, due to the large number of altered nerve cells.…”
mentioning
confidence: 99%